Associations of private residential gardens versus other greenspace types with cardiovascular and respiratory disease mortality: Observational evidence from UK Biobank. (September 2022) - Roscoe, Charlotte; Mackay, Catriona; Gulliver, John; Hodgson, Susan; Cai, Yutong; Vineis, Paolo; Fecht, Daniela
Abstract: Background: Longitudinal evidence linking urban greenspace to reduced rates of all-cause and cause-specific mortality has mostly been established using greenness measures of limited specificity such as vegetation indices. Evidence on specific green space types, including private residential gardens is less well established. Methods: We examined associations of greenspace with all-cause, non-injury, cardiovascular disease (CVD) and respiratory disease deaths in UK Biobank – a national prospective cohort of adults with linked Office for National Statistics mortality records. We included private residential gardens and other greenspace types, e.g., public parks, sport facilities, using categories from Ordnance Survey MasterMap™ Greenspace. We used Cox proportional hazards models, adjusted for individual and area-level covariates, and stratified analyses by sex, household income, and area-level deprivation. In sensitivity analyses, we further adjusted for air pollution, road-traffic noise, indirect tobacco smoke exposure, and physical activity, and restricted analyses to non-movers. Results: In 232, 926 participants, we observed 13, 586 all-cause, 13, 159 non-injury, 2, 796 cardiovascular (CVD), and 968 respiratory disease deaths. Private residential garden cover showed inverse associations with all-cause, non-injury, CVD, and chronic respiratory disease mortality, after adjustment for covariates and other types of greenspace, with hazard ratios and 95 % confidence intervals of 0.94 (0.91, 0.97), 0.95 (0.92, 0.97), 0.92 (0.86, 0.98) and 0.87 (0.78, 0.98), respectively, per interquartile range (IQR) increase in private residential garden cover (IQR = 21.6 % increase within 100 m buffer). Other greenspace types showed weaker inverse associations with CVD and chronic respiratory disease mortality than private residential gardens. Sex, household income, and area level deprivation modified associations. Findings were robust to sensitivity analyses. Conclusion: Our finding that private residential gardens substantially contributed to inverse associations of total greenspace with premature mortality has implications for public health and urban planning. Inequities in access, ownership, views and use of private residential gardens, and potential health inequities, should be addressed.